FEATURES OF SPREAD OF IPS ACUMINATUS GYLL. IN PINE STANDS OF EASTERN POLISSYA - Porohnyach, I. V. (Forestry and Forest Melioration, 2018)
Introduction Recently, the areas of pine stands with local decline foci have significantly increased in Eastern Polissya (Ukraine). The decline of trees is brought about by the Ips acuminatus Gyll species colonizing the trees. During the first years, dead trees appeared singularly or in groups, mainly focusing on the forest border of the southern and southwest exposition near open areas (frames, glades, fields, rides, etc.). Then focuses have rapidly begun expanding, turning into the group type, and, in some cases, into the continuous type. The aim of the research was to clarify the peculiarities of biology and distribution of Ips acuminatus in the pine stands in Eastern Polissya and use them in order to define the best timing to take measures for improving health condition. Materials and Methods We did research in pine stands of different ages with focuses of group drying of trees. To assess the population indexes of Ips acuminatus, we applied generally accepted methods of forest-pathological and entomological research. Results During the growing season two generations of Ips acuminatus are completed in Eastern Polissya: spring generation (during May-June) and summer one (during July-August). The young generation that colonized the pine trees of the III–IV health condition categories in the autumn (September-October) hibernates at the stages of larvae and young imago under the bark. Tree colonization by Ips acuminatus begins from the top of the steam. As the tree dies, the population gradually extends down along the steam but not below the border of the transitional and coarse bark area – to the relative height of the tree of 0.2. At the same time, the largest population was concentrated in the area of the thin bark of the upper part of the trunk at the relative height of 0.5–0.8. The most nutritious substrate for the development of a young generation is located in this zone. By means of the laboratory analysis we found out that the population of the Ips acuminatus young generation in the thin bark in mature stands varied, on average, from 41 to 100 individuals per dm2. These indexes exceeded the average population characteristics of the species by 4–9 times, indicating the initial phase of outbreaks of Ips acuminatus. In young stands the production rate was slightly lower, namely it varied from 31 to 47 individuals per dm2 since the energy nutrient value of small trunks is smaller than that of large trees. The average density of the parent-generation population of Ips acuminatus in the decline foci in the mature pine stands ranged from 5.5 to 7.4 individuals per dm2. The average length of the egg gallery in the colonized trees ranged from 4.5 to 5.0 cm, which is lower than that of this species due to the high population density. Autumnal generation at the larvae stage hibernates under the bark of the colonized trees in the transitional bark area – at the relative height of the tree of 0.2-0.35. Conclusions In 2017-2018, the population indexes of Ips acuminatus in Eastern Polissya indicated an outbreak of the reproduction and increase in density in the foci of drying in pine stands. Therefore, we recommend selective sanitary felling during the autumn-winter period in order to extract pine trees freshly colonized by bark beetles and to minimize the number of pests before the onset of its mass fly in the spring. Taking into account a rapid reproduction of spring and summer populations of Ips acuminatus, it is necessary to timely remove the pine trees freshly colonized by bark beetles during the growing season. These measures will help prevent the development of a younger generation of pests, a further increase of their number and colonization of healthy pine trees along the periphery of the decline foci. 1 Fig., 2 Tables, 8 Refs.